2022
DOI: 10.1155/2022/6151866
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness and Safety of Mesenchymal Stem Cells in the Treatment of Osteoarthritis: A Systematic Review and Meta-analysis of 28 Randomized Controlled Trials

Abstract: Objective. To evaluate the effectiveness and safety of mesenchymal stem cells (MSCs) in the treatment of osteoarthritis (OA). Methods. Chinese databases (such as CNKI and SinoMed) and English databases (such as PubMed and Embase) were searched to collect randomized controlled trials (RCTs) of MSCs in the treatment of OA. The retrieval time is from inception to October 10, 2021. The literature was strictly selected according to the inclusion and exclusion criteria, data was extracted, and the quality was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Conversely, Long et al [ 105 ] showed that stem cells improved patients WOMAC scores better than conventional treatment (WMD = − 3.81; 95% CI [− 6.95, − 0.68]. At 6 months, only three studies [ 100 , 101 , 105 ] and at 12 months, only five [ 94 , 100 , 101 , 103 , 105 ] demonstrated that stem cells significantly improved patients WOMAC scores (Fig. 2 ).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Conversely, Long et al [ 105 ] showed that stem cells improved patients WOMAC scores better than conventional treatment (WMD = − 3.81; 95% CI [− 6.95, − 0.68]. At 6 months, only three studies [ 100 , 101 , 105 ] and at 12 months, only five [ 94 , 100 , 101 , 103 , 105 ] demonstrated that stem cells significantly improved patients WOMAC scores (Fig. 2 ).…”
Section: Resultsmentioning
confidence: 98%
“…At 3 months, the results from Qu et al [ 93 ] showed that stem cells were less effective than conventional treatment in improving the patients WOMAC scores (WMD = 3.35; 95% CI [0.01, 6.69]). Conversely, Long et al [ 105 ] showed that stem cells improved patients WOMAC scores better than conventional treatment (WMD = − 3.81; 95% CI [− 6.95, − 0.68]. At 6 months, only three studies [ 100 , 101 , 105 ] and at 12 months, only five [ 94 , 100 , 101 , 103 , 105 ] demonstrated that stem cells significantly improved patients WOMAC scores (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations